Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Pegawai Dimediasi oleh Organizational Citizenship Behavior pada Badan Kepegawaian dan Pengembangan Sumberdaya Manusia Kabupaten Bombana - Andi Alamsyah Idris; Ibnu Hajar; Asraf (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine and explain the effect of transformational leadership on employee performance. The effect of transformational leadership on organizational citizenship behaviour. The effect of organizational citizenship behaviour on employee performance. The effect of transformational leadership on employee performance is mediated by organizational citizenship behaviour. The research design used is quantitative research. The population in this study were employees of the Staffing and Human Resources Development Agency (BKPSDM) of Bombana Regency totalling 35 people. The sampling technique used saturated sampling technique. Data collection used a questionnaire through a Likert scale. The data analysis technique used SEM-PLS 4. The results showed that transformational leadership has a positive and significant effect on employee performance. Transformational leadership has a positive and significant effect on organizational citizenship behaviour. Organizational citizenship behaviour has a positive and significant effect on employee performance. Transformational leadership has a positive and significant effect on employee performance mediated by organizational citizenship behaviour or partial mediated.